(3eWGdY GdCfhGQ heSGdc GdCHQGQ aj aVGFd GdUdGI Ydi GdQShd Udi dGdg Ydjg hSde hYdi Bdg hUMHg hSdes - (3GdbQWHj , LHQ Hf eMeO Hf LHQ Hf gTGe, CHh eMeO,J (B615 (3g` s
(3ChdgG (B:s
(3bGd GdYHO GdabjQ GdePfH LHQ HfGdbQWHiGdMeO ddg Gdedc GdbOhS Ph GdLdGd hGdEcQGe s
(3BNQgG (B:s
(3hgPG eG Ydb Ydi Bdg hUMHg hSde JSdjekG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B43 - (3U(B83s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B108 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B109s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY e (B15) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs